2017
DOI: 10.2527/jas2016.0498
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of dietary protein and dried citrus pulp levels on growth performance, small intestinal morphology, and hindgut fermentation of weanling pigs

Abstract: Weanling pigs ( = 108, 21 d of age, 5.82 ± 0.16 kg initial BW) were assigned to a 2 × 2 factorial arrangement of treatments to evaluate the effects of dietary levels of CP (high- and low-CP diets) and dried citrus pulp (DCP; 0% and 7.5%) on growth performance, small intestinal morphology, and hindgut fermentation. Pigs were blocked by initial BW and allotted to 1 of 9 pens, each containing 3 pigs. The high-CP diets consisted of feeding 20% and 21% CP levels throughout phase 1 (0 to 14 d) and phase 2 (14 to 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Therefore, the present study was designed to determine the effects of supplementation of fermented medicinal plants in diet containing dried citrus pulp in growingfinishing pigs. Our data indicated that dietary inclusion of dried citrus pulp at 10% had no detrimental effects on ADG, ADFI, and G:F. In agreement with the results of the current experiment, previous studies with weanling pigs (7.5% dried citrus pulp; Almeida et al 2017) and finishing pigs (15% dried citrus pulp; Crosswhite et al 2013) demonstrated that citrus pulp could be used in weanling and finishing pig diets without impairing growth performance. Conversely, several studies indicated that dietary inclusion of citrus pulp had negative effects on animal growth performance.…”
Section: Growth Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the present study was designed to determine the effects of supplementation of fermented medicinal plants in diet containing dried citrus pulp in growingfinishing pigs. Our data indicated that dietary inclusion of dried citrus pulp at 10% had no detrimental effects on ADG, ADFI, and G:F. In agreement with the results of the current experiment, previous studies with weanling pigs (7.5% dried citrus pulp; Almeida et al 2017) and finishing pigs (15% dried citrus pulp; Crosswhite et al 2013) demonstrated that citrus pulp could be used in weanling and finishing pig diets without impairing growth performance. Conversely, several studies indicated that dietary inclusion of citrus pulp had negative effects on animal growth performance.…”
Section: Growth Performancesupporting
confidence: 92%
“…Citrus pulp, a by-product from citrus juice industry, has been used in livestock feeding, especially in ruminants diets (Bampidis and Robinson 2006;Villarreal et al 2006;Caparra et al 2007;Oni et al 2008;Gouvêa et al 2016;Gobindram et al 2017). However, several studies indicated that citrus pulp can be included in monogastric animal diets to reduce feed costs (Cerisuelo et al 2010;Strong et al 2015;Almeida et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The papers that both assessors assessed affirmatively for all questions were included in the analysis, yielding 28 papers. These articles were Nielsen et al (2001), Houška et al (2004, Wellock et al (2008), Li et al (2008), Kutzer et al (2009), Zonderland et al (2010), Fels et al (2012, Madsen & Bee (2014), Bell et al (2015), Baldinger et al (2016), Van Wettere et al (2016, Almeida et al (2017), Vanrolleghem et al (2019, Montsho et al (2016), Kalita et al (2015), Jin et al (2019), Tsourgianis et al (2004, Devillers and Farmer (2009), Bohnenkamp et al (2013) Using Excel® software, the data regarding the impact of weaning age on piglet performance were organized for statistical analysis. The variables were tested for normality of the residuals using Shapiro-Wilk test and homogeneity of variance using Levene's test.…”
Section: Methodsmentioning
confidence: 99%